Pengembangan E-Modul An-Nur dengan Menggunakan Book Creator untuk Meningkatkan Hasil Belajar Siswa - Azizah, Laily Nur; Budiwan, Jauhan; Fikriawan, Suad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to develop and test the feasibility and attractiveness of e-module learning media by using book creators in the SKI subject of Sunan Kudus Class VI material. The type of research used is research and development (R&D). The development model uses the ADDIE development model adopted in Robert Maribe Brach. Media eligibility is based on the results of validation and media attractiveness based on student pre-test and Post-test results and media attractiveness response questionnaires. The effectiveness of the e-module was tested with nonequivalent control group design and t-test with SPSS program. The results showed that the results of media validation got a score of 85.45%, the results of material validation got a score of 91.30% with very feasible criteria, and the response of media attractiveness for students got a score of 80.87% with interesting criteria. Based on the t-test, a Sig. (2-tailed) value of 0.000 < 0.05 was obtained, it can be concluded that there is an influence of the An-Nur e-Module using Book Creator on improving student learning result. The improvement in student learning result can be seen in the paired samples statistics table that the experimental class pre-test score is 58.61 and the experimental class Post-test is 84.52, and (5) the experimental class Post-test results are 84.52 and the control class Post-test group is 75.82. Thus, that the level of learning result among students with An-Nur e-Module is higher than students with conventional learning